Breaking the Dullness of Thought Among Nahdliyin: The Genealogy of KH. Sahal Mahfudh's Civilization Jurisprudence - Mohammad Rif’an Asofik; Ahmad Khafidh (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2023)
This article discusses the central role of the KH. Sahal Mahfudh as a breaker of thought dullness among Nahdliyin through a genealogical approach to the jurisprudence of civilization. Nahdlatul Ulama (NU), one of the largest Islamic organizations in Indonesia, plays a significant role in shaping the religious identity and civilization of society. However, like other organizations, NU also face challenges in the face of rapid social, political, and technological changes. KH Sahal Mahfudh, a renowned scholar and NU leader, became a key figure who carried out the mission of renewing the understanding of jurisprudence among Nahdliyin. This article describes the genealogy of jurisprudence thought among Nahdliyin since the beginning of NU to KH. Sahal Mahfudh's role as a pioneer in reviving and renewing scientific discourse within the NU. Through the genealogy analysis method, this article traces the origins of jurisprudence in Nahdliyin and examines its development from time to time. The results show that over time, jurisprudent thinking among Nahdliyin tends to experience stagnation, especially in dealing with contemporary issues. This poses a challenge to answering the problems of Islamic laws that are relevant to the context of the times. KH Sahal Mahfudh, with his progressive and inclusive vision, succeeded in offering a jurisprudent approach that is relevant and adaptive to changing times. Through his work, he invited Nahdliyin to re-explore the roots of authentic Islamic science, while still paying attention to the context of modern civilization. KH. Sahal Mahfudh's important contribution to developing scientific discourse among Nahdliyin helped unravel the stagnation of thought and paved the way for the continuous renewal of Islamic thought. Thus, this article provides insight into the importance of the renewal of thought among Nahdliyin, especially in the context of modern civilization. The genealogy of civilization jurisprudence is described through the role of KH. Sahal Mahfudh provided a valuable contribution to understanding the dynamics of Islamic thought in Indonesia, as well as its relevance in facing various contemporary challenges.